Montmorillonite K10 as an Efficient and Reusable Catalyst for the Synthesis of Substituted Pyrazolo[3,4-d]pyrimidin-4-ones Under Solvent-Free Conditions - Davoodnia, A.; Moloudi, R.; Tavakoli-Hoseini, N.; Shaker, M. (Asian Journal of Chemistry, 2012)
A green and efficient method for the synthesis of pyrazolo[3,4-d]pyrimidin-4-ones through heterocyclization reaction of 5-amino-1-phenyl-1H-pyrazole-4-carboxamides with orthoesters using Montmorillonite K10, as an effective and reusable catalyst, under solvent-free conditions is described. The present methodology offers several advantages, such as a simple procedure with an easy work-up, short reaction times, high yields and the absence of any volatile and hazardous organic solvents. Furthermore, the products could be separated simply from the catalyst and the catalyst could be recycled and reused with only slight reduction in its catalytic activity.